2021
DOI: 10.48550/arxiv.2108.01206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coherent spin-spin coupling mediated by virtual microwave photons

Patrick Harvey-Collard,
Jurgen Dijkema,
Guoji Zheng
et al.

Abstract: We report the coherent coupling of two electron spins at a distance via virtual microwave photons. Each spin is trapped in a silicon double quantum dot at either end of a superconducting resonator, achieving spin-photon couplings up to around gs/2π = 40 MHz. As the two spins are brought into resonance with each other, but detuned from the photons, an avoided crossing larger than the spin linewidths is observed with an exchange splitting around 2J/2π = 20 MHz. In addition, photon number states are resolved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Despite the fact that hybrid spin qubits are more prone to charge noise, references [34,35] have achieved the strong coupling regime, i.e., the spin-photon coupling rate is greater than the spin decoherence rate and the cavity loss rate. Recently, Borjans et al [37], demonstrated that one can coherently couple two spin qubits with a resonator by extending the architecture in [34] and Harvey-Collard et al [38] reported the coupling of distant spins through virtual photons. The latter represents a significant step towards the experimental realisation of cavity-mediated two-qubit gates.…”
Section: A Overviewmentioning
confidence: 99%
“…Despite the fact that hybrid spin qubits are more prone to charge noise, references [34,35] have achieved the strong coupling regime, i.e., the spin-photon coupling rate is greater than the spin decoherence rate and the cavity loss rate. Recently, Borjans et al [37], demonstrated that one can coherently couple two spin qubits with a resonator by extending the architecture in [34] and Harvey-Collard et al [38] reported the coupling of distant spins through virtual photons. The latter represents a significant step towards the experimental realisation of cavity-mediated two-qubit gates.…”
Section: A Overviewmentioning
confidence: 99%
“…By using nuclear spin-free 28 Si [3], the spin qubit dephasing time is significantly increased, as it is no longer limited by hyperfine interaction with remaining 29 Si, but by charge noise, which couples via local magnetic field gradients [4][5][6][7]. The fidelity of single-qubit [5,[8][9][10] and two-qubit gates [11] already exceeds the quantum error correction threshold [12]. Simple two-qubit gates require an overlap of the electron wave-function [13][14][15], which would require a very dense two-dimensional qubit matrix, in which topological quantum error correction can be realized [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Driven by significant technological progress in enhancing the amplitude of spin-photon interactions [42][43][44], coupling distant spin qubits via microwave resonators is an appealing approach [45]. In analogy to superconducting circuits [46,47], current spin-photon interfaces are designed to be transversal, where nearly resonant photons flip the spin state.…”
mentioning
confidence: 99%